Corrosion Control in CO2 Enhanced Oil Recovery From a Perspective of Multiphase Fluids - Wang, Zi Ming; Song, Guang-Ling; Zhang, Jian (Frontiers in Materials, 2019)
Carbon capture and storage (CCS) combined with CO2-enhanced oil recovery (EOR), has been recently viewed as an economical and effective method for the reduction of carbon emissions. However, corrosion is a challenging issue in the whole chain process of CO2-EOR production if water presents and mild steel pipeline is used. In this paper, the corrosion risk of pipeline at different stages of CO2-EOR production is systematically assessed based on a detailed analysis of the fluid characteristics. According to the fluid state of CO2, water and crude oil, current understandings on the corrosion behavior of steel materials in multiphase flow conditions are reviewed. Furthermore, the intermittent water wetting phenomena and the fluid behavior of water droplets or clusters in an electrolyte/non-electrolyte emulsion are correlated with the steel corrosion performance, providing new insights into the corrosion phenomena. Besides application of corrosion resistant materials and selection of corrosion inhibitors, tailoring of processing parameters, such as enhancing the water entrainment, shortening the water contact time, and reducing the solution corrosivity, is highly recommended as an effective method for corrosion control in aggressive CO2-EOR production conditions. Based on these, some important future research topics on the corrosion in multiphase fluids are suggested.